ICT Adaptation in ERL-Based Learning During the COVID-19 Pandemic - Mariyudi Mariyudi; Halimatus Sakdiah; Teuku Fadhla; Ikramuddin Ikramuddin (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
The purpose of this study is to produce a learning strategy formulation through ICT media based on Emergency Remote Learning (ERL) in an effort to strengthen post-pandemic learning and support the Merdeka Belajar program. This study uses a theoretical and methodological research approach, which mostly uses a deductive theoretical and qualitative methodological approach, including the SWOT matrix analysis. The structural questionnaire link was designed using a 'Google form' which was sent to 500 high school students and teachers. The test results show that the level of student satisfaction in ICT Adaptation on ERL Based Learning obtained that students are satisfied with the ICT Adaptation on ERL Based Learning experience and no serious obstacles were found during the teaching-learning process during the COVID-19 pandemic except for inadequate interaction between students and teachers, as well as social interaction between students. Alternative strategies in the ICT adaptation on ERL-Based learning formulated using a SWOT matrix analysis approach have been presented with the hope that policymakers feel more confident in their decision-making.